Obrazy (z) Arkadii. Jewreinowa sceniczne wspomnienia o Rosji - Gracla, Jadwiga (Acta Polono-Ruthenica, 2018)
In this article, the author analyzes selected aspects of two dramas of Evreinov from the émigré period: What has no name and Citizens of the second category. One of the principles of constructing their theatrical space is, in the author’s opinion, the principle of memories, which takes place on the stage, transferring the world remembered to the universe of theater. Thus understood, the dramas become not only a testimony to Evreinov’s interest in the transformation of the theater but there is also the unusual testimony of his journal, an album of photographs. Images from the past are kept in these photos, but at the same time they are a warning against rejecting the present, because, as the author shows, such a world can only exist in the theater. The paintings are doubly processed: through memory and through the theater.